Place of death, end-of-life transitions and cognition: a population cohort aged 85 and older. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Perrels, Anouk; Fleming, Jane; Zhao, Jun; Farquhar, Morag; Barclay, Stephen
Abstract : Background: Despite fast-growing 'older old' populations, place of care trajectories for very old people approaching death with or without dementia are poorly understood. This study compares place of death and end-of-life transitions in place of residence experienced by 'older old' people of different cognitive status and, if ascertainable, dementia status. Methods: Descriptive analysis of prospectively collected data linked with mortality records of n=283 participants in the UK population-based Cambridge City over-75s Cohort (CC75C) with cognitive assessments <1year before they died aged ≥85 (n=104 of known dementia status). Results: 69% were community-dwelling (home/sheltered housing) <1year before death, as were 40% of those with severe cognitive impairment or dementia. By the time of death only a small minority had changed address, according to their 'usual address' on death registration. However, for 55% this 'usual address' was not the place of death: in the period leading up to death over half moved their place of residence or care and died away from their 'usual address' (72% from community addresses, 20% from institutions). This discrepancy was greatest for those with intact cognition. Hospital was the most common place of death for all but the most cognitively impaired, whereas for individuals with severe cognitive impairment or dementia it was a care-home. Conclusion: These results provide important information for planning end-of-life services. The majority of very old community-dwelling individuals, especially those with severe cognitive impairment, died away from home, perhaps suggesting insufficient support in the period prior to death. Findings also suggest long-term care but not sheltered settings may avoid acute hospital admissions. Further research is needed on the effect of care transitions on people with cognitive impairment and dementia. Complex care needs of 'older old' people approaching death may involve a change in locus of care: more individualised end-of-life care approaches are needed in all settings.